PENTINGNYA MEREFORMASI PENDIDIKAN DI INDONESIA - Isfironi (Al'Adalah, 2015)
Education reform is a demand along with social changes that occurred in indonesia .The crisis multidimensional occurring caused by the loss of the substance of education lasting. Education moral values no longer be important, whereas the erosion of moral and spiritual values will make people more pragmatic and opportunistic. The future of the nation being gamble in education reform now. Joints in the life of nation and State of Indonesia should be reinforced through quality education and competitive by strengthening brain intelligence, values, and spiritual. Human image should be changed to Indonesia which has human personality and by avoiding the dehumanizing system.